2010
DOI: 10.5005/jcdp-11-4-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Surgical Morbidity Associated with Mandibular Third-Molar Surgery in Young and Aging Populations

Abstract: Aim: Prophylactic surgical extraction of impacted third molars is a common practice throughout the world justified on the presumption that the risk of surgical morbidity increases with increasing age, among other reasons. The aim of this study was to analyze and compare surgical morbidity associated with third-molar extractions in young and aging populations. Methods and Materials:A review of records for all patients who underwent the surgical extraction of impacted third molars between April 2001 and June 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Many authors identified a positive link between age and pain . Nevertheless, several other researchers found no pain‐related role of age . Capuzzi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many authors identified a positive link between age and pain . Nevertheless, several other researchers found no pain‐related role of age . Capuzzi et al .…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that only few patients in the old age category had periapical periodontal cysts and this accounted for the limited number of complications in this category. However, some researchers [26,27] believed that increased age even above 40 years does not predispose subjects to additional surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…[11], the average age at which surgery of M3 was performed was 49 ± 3 years and for these authors there is an increase in the incidence of fractures and their possible risk, especially in males with full dentition, for those patients older than 40 years. By contrast, in some studies no difference in incidence between patients who are 40 years old or older and those under 40 years emerges [18]. …”
Section: Discussionmentioning
confidence: 99%